Analisis Wacana Kritis Berita “Mahfud MD: Pemerintah Tak Setengah-Setengah Tindak Pelaku Investasi Ilegal” di Kumparan.com - Abu Setiawan Pratama; Ferry Darmawan (Bandung Conference Series: Journalism, 2022)
Abstract. Illegal investment under the guise of binary options is currently being discussed in the community. This issue has also become the main topic of news coverage in online news portal in Indonesia. The online news portal Kumparan is one of the online news portal that reports about this case of illegal binary options investment. The discussion about illegal binary options investment is inseparable from the two cases of arresting influencers who were caught in illegal investment cases. The first case ensnared Indra Kesuma who was proven guilty of fraudulent binary options investment through the Binomo application. Then, the second case ensnared Doni Salmanan who was also proven to have committed a binary option investment fraud through the Quotex application. This study uses a descriptive qualitative research method with a critical paradigm approach. The researcher will use the theory of Critical Discourse Analysis of the Teun A. Van Dijk model by taking one of the news uploaded on the online news portal Kumparan entitled "Mahfud MD: The Government Is Not Half-Half Acts of Illegal Investment Actors". By using critical discourse analysis, it is expected to reveal linguistic rules that construct discourse, produce discourse, understand discourse, and symbolize something in discourse. Abstrak. Investasi ilegal berkedok binary option saat ini ramai diperbincangkan di tengah-tengah masyarakat. Isu ini pun menjadi topik utama pemberitaan di berbagai portal berita online di Indonesia. portal berita online Kumparan menjadi salah satu portal berita online yang memberitakan mengenai kasus investasi ilegal binary option ini. Ramainya perbincangan mengenai investasi ilegal binary option ini tak lepas dari dua kasus penangkapan influencer yang terjerat kasus investasi ilegal. Kasus pertama menjerat Indra Kesuma yang terbukti melakukan penipuan investasi binary option melalui aplikasi Binomo. Lalu, kasus kedua menjerat Doni Salmanan yang juga terbukti melakukan penipuan investasi binary option melalui aplikasi Quotex. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan pendekatan paradigma kritis. Peneliti akan menggunakan teori Analisis Wacana Kritis model Teun A. Van Dijk dengan mengambil salah satu berita yang diunggah di portal berita online Kumparan yang berjudul “Mahfud MD: Pemerintah Tak Setengah-Setengah Tindak Pelaku Investasi Ilegal”. Dengan menggunakan analisis wacana kritis diharapkan dapat mengungkapkan kaidah kebahasaan yang mengonstruksi wacana, memproduksi wacana, memahami wacana, dan melambangi suatu hal dalam wacana.